Hubungan Pola Asuh Orang dengan Pertumbuhan Balita di Desa Kasukia Kecamatan Wonggeduku Barat Kabupaten Konawe - Nofitasari, Ari (Jurnal Gizi Ilmiah, 2016)
Parenting is a pattern of interaction between parents and children, namely how the attitude or behavior of parents when interacting with children, including how to apply rules, teach values ​​/ norms, give attention and affection and show good attitudes and behavior so that they are used as role models for their children. . The data obtained at the Wongeduku Barat Public Health Center were 31 children under five who experienced growth disorders. The purpose of this study was to determine the relationship between parenting and the growth of children under five in Kasukia Village, West Wongeduku District, Konawe Regency. This research is an analytic study using the Cross Sectional Study design method. The population in this study were all mothers who had toddlers aged (12 – 59 months) who lived in Kasukia Village, Wongeduku Barat District, Konawe Regency as many as 51 people and the sample in this study was There are 45 mothers who have toddlers in Kasukaia Village using the Random Sampling technique. The statistical test used is Chi Square to see if there is a relationship between the independent variables and the dependent variable. The results of statistical tests show that there is a relationship between the dependent variable and the independent variable with the value of each variable, feeding (X2 count = 5,314), education (X2 count = 4,148), health care (X2 count = 3,907) with toddler growth. Thus it can be concluded that there is a relationship between the provision of food, education, health care and the growth of children under five. It is hoped that mothers will provide better care so that their toddler's growth does not experience disturbances